Improving the system of labor standards in forest nursery - Panyavina Ekaterina; Tseplyaev Alexey (BIO Web of Conferences)
Improving the labor standardization system in forest nurseries requires regular revision and updating of the current regulatory framework. The study is aimed at assessing the state of the existing labor standardization system at forestry enterprises producing planting material. The relevance of improving the labor standardization system in forest nurseries is confirmed in connection with the introduction of new production technologies and the use of new equipment in their activities, as well as the orientation of enterprises to increase labor productivity and improve accounting processes of activities. The necessity of defining labor standards for the operation of digging large-sized planting material is substantiated, a step-by-step description of the labor standardization process for this operation with the selection of necessary measures and methods is given. The optimal composition of work on digging large-sized trees is determined and a photograph of working time is taken, which will allow determining the optimal structure of labor time costs. The labor intensity of digging one unit of large-sized forest planting material is determined. The obtained results open up new directions of scientific research in determining time standards and production standards for forestry work.